Strategies for enhancing the effectiveness of e-learning courses in medical education and health professions education - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2021)
E-learning refers to the employment of technology to facilitate access to learning resources on the internet to enhance acquisition of new knowledge, skills and/or behavior. It is very important to develop an understanding about the process involved in the development of an e-learning strategy, and it has to start with analyzing the existing situation and how e-learning can bridge the gap. Regardless of the e-learning course, if the organizers want to ensure that participants are maximally benefited, it is essential that the organizers take efforts to know their participants, especially in terms of their learning behaviors and needs, so that these areas can be targeted during the course. Finally, the organizers should be always aiming for the improvement of the program through modifications in the program based on the feedback received from the participants. In conclusion, e-learning is an important addition in the delivery of the medical curriculum or the health professions education. However, it is crucial for the organizers to adopt different strategies to ensure that the overall effectiveness of the program can be enhanced and the intended objectives are accomplished.